The potential impacts of the songbird trade on mixed-species flocking. (June 2018) - Marthy, William; Farine, Damien R.
Abstract: Mixed-species flocking is an important avian social system that supports a large number of species. Current reviews of threats to mixed flocks have only examined two types of anthropogenic pressures: different land use intensity and fragmentation. We highlight the bird trade as another major potential threat for many mixed-species flocking species in Southeast Asia. We examine the potential indirect impact of the bird trade by comparing social networks of flocking data collected over two periods nearly 20 years apart (1997 and 2016) from the same site in Sumatra, Indonesia. We find that the structure of the two networks was significantly correlated. However, of the 90 species observed, 49 had previously been identified as part of the bird trade. These species experienced a significantly greater decrease in network centrality over time compared to the non-traded species, resulting in a loss of structure in the mixed-species flocking network. Simulating further disturbances suggests that flocks may not be resilient to the complete loss of two or more traded species. Our results suggest that trapping is likely to be contributing to the degradation of flocks, and ultimately could lead to the widespread declines in those other species that also rely on mixed-species flocking.